Development of Tourism Village Potential in Teluk Jering Hamlet, Kenidai Village, Tambang District, Kampar Regency - Supeno, Bambang; Burhan; Oemar, Fahmi; Heri, Helwen; Seswandi, Agus; Anggraini, Nia (PT FORMOSA CENDEKIA GLOBAL, 2025)
This community service project enhanced the capacity of tourism operators in Pulau Cinta, Teluk Jering, through structured mentoring on ecotourism management. Activities included preparation, socialization, module development, and mentoring sessions. Key topics covered sustainable ecotourism practices, organizational structure, and operational management. Results showed improved understanding, better organizational frameworks, increased operational efficiency, and enhanced practical skills. Active discussions and stakeholder collaboration contributed to sustainable ecotourism development. To ensure long-term impact, continuous mentoring, digital marketing integration, and financial management training are recommended for Pulau Cinta’s sustainable growth